A Comprehensive Review of the Impact of Thermal Radiations on Energy Exchange Systems - Muhammad, Ashraf (The Nucleus, 2023)
Radiations or electromagnetic rays have a significant role in energy emission from nuclear explosions as well as energy transmission in furnaces and combustion chambers. The radiations are considered in computing thermal influence in devices such as a rocket nozzle, nuclear power plants for space applications, or a gaseous-core nuclear rocket. Energy is transferred between separated elements without a medium in case of radiations or electromagnetic rays. The structure, surface quality, temperature and wavelength of the rotation angle at which radiation is emitted or absorbed by the surface and the spectral distribution of the radiation encountered on the surface are only a few of the variables that affect the radiative behavior. In some important situation, heat is transferred within the solid media or highly viscous media is considered so that convection in the medium is not important. The combined radiation-conduction is important in glassy materials and can be used as a coating to protect the interior of a body from high external temperature. Also, the radiation-conduction process plays a crucial role in controlling how hot or cold the ablating layer is. In these circumstances, the temperature distribution has an impact on how the ablating substance will melt, soften or evaporate. The main novelty of the current work is to highlight the important aspects of thermal radiation effects on heat transfer mechanism and to focus on recent developments in this field.